(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: THilnahyroid cancer is a cancer that starts in the thyroid gland and thought to be related to a number of environmental and genetic predisposing factors .Human Papil- loma Virus (HPV) the virus that causes cervical cancer ,is also linked to throat cancer and is one among their associated infective agents. Objective: This study aimed at detecting DNA of HPV genotype-18 using in situ hybridization technique in thyroid tissues from benign thyroid hyperplasia and thyroid car- cinoma, and elucidate the association between this HPV-18 and thyroid carcinogenesis. Patients and Methods: Sixty (60) formalin-fixed, paraffin embedded thyroid tissue blocks were obtained ,among them (30) tissue biopsies from thyroid carcinoma with grade I and (20) benign thyroid neoplasm tissue blocks as well as (10) autopsies from apparently normal thyroid tissues were collected from the archives of Forensic Medicine Institute / Babil and used as thyroid healthy control group. Detection of HPV-18 was done by using highly sensitive version of in situ hybridization technique. Results: Among malignant thyroid tumors 56.7% patients had HPV-18 while 35% HPV- 18 positivity was detected in benign thyroid tumor group. None of healthy thyroid tissues revealed ISH reactions. There was 32.7% female had HPV-18, and 24% male had HPV-18. No significant statistical associations were noticed between the presence of HPV-18 and the age of those patients. Conclusion: Human Papilloma virus genotype-18 could share a role in pathogenesis of this group of patients with thyroid cancers.